2013
DOI: 10.1007/s10342-013-0726-x
|View full text |Cite|
|
Sign up to set email alerts
|

Responses of small mammals to clear-cutting in temperate and boreal forests of Europe: a meta-analysis and review

Abstract: We analyzed the responses of small mammals to clear-cutting in temperate and boreal forests in Europe. We conducted a meta-analysis of published research on most often studied small mammal species (the striped field mouse, the yellow-necked mouse, the wood mouse, the field vole, the common vole, the bank vole, the Eurasian harvest mouse, the common shrew and the Eurasian pygmy shrew), comparing their abundance on clear-cuts and in unharvested stands. For four other species (the gray-sided vole, the Siberian fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 107 publications
(128 reference statements)
0
12
1
Order By: Relevance
“…Clearcut treatments were created by removing the canopy in a single harvest and were found to have a negative effect on mammal detection. However, clearcut sites have shown a positive effect on small mammals in boreal and temperate forests of Europe (Bogdziewicz and Zwolak, 2014). This difference between Europe and the plots in this study was most likely due to the lack of habitat for the specific mammal species detected.…”
Section: Discussioncontrasting
confidence: 53%
“…Clearcut treatments were created by removing the canopy in a single harvest and were found to have a negative effect on mammal detection. However, clearcut sites have shown a positive effect on small mammals in boreal and temperate forests of Europe (Bogdziewicz and Zwolak, 2014). This difference between Europe and the plots in this study was most likely due to the lack of habitat for the specific mammal species detected.…”
Section: Discussioncontrasting
confidence: 53%
“…In terms of associations with covariates (Supplementary Material 4 ), the estimated higher risks in districts exhibiting greater deforestation, lower annual temperatures, and higher relative humidity were related to the ecology of the striped field mouse. As a generalist species, this mouse is resilient in deforested and disturbed areas and has even increased in abundance 21 . A previous study suggested that the risk of scrub typhus, of which the striped field mouse is a major reservoir, tended to increase in habitats with greater deforestation 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cover forestry will also result in a permanent presence of dying trees (caused by self-thinning) of smaller diameter as well as stumps from selective cuttings, thus providing natural enemies with alternative resources or microhabitats. During the first years after the disturbance by clear-cutting, the early successional flowering herbs and grasses are thriving and may provide food for parasitoids (Rubene et al, 2015) and vertebrate omnivores like small mammals that may prey on pests (Michał and Rafał, 2013).…”
Section: Rotation Lengthmentioning
confidence: 99%